SITUS INVERSUS TOTALIS WITH UNILATERAL UNDESCENDED TESTIS: A CASE REPORT - Ain, Qurat-ul; Bashir, Noman; Sohail, Talha; Siddiqa, Somayya; Malik, Nazir Ahmed (Journal of Postgraduate Medical Institute, 2024)
Situs Inversus Totalis (SIT) is a rare genetic anomaly that causes the heart and abdominal viscera to be positioned in a mirror image of their regular positions. It may present alone or in association with various associated anomalies. Most patients present with no symptoms and are often diagnosed incidentally; however, some have co-existent anomalies and must be ruled out. A male neonate weighing 3.2 kg delivered at term via Em-LSCS presented with transient tachypnea of the newborn (TTN) and was on oxygen dependence in the neonatal intensive care unit (NICU). A General Physical Examination revealed heart sounds on the right side of the chest and empty left scrotal sac. Chest X-ray was done that showed Situs Inversus Totalis and congenital pneumonia. Ultrasonography of the scrotum revealed the absence of the left testis. Situs Inversus Totalis should be evaluated and investigated to rule out associated anomalies, even when the finding is incidental. It is recommended that physicians promote regular medical examinations for their patients, since this practice can aid in the detection of anomalies, hence mitigating the risk of incorrect diagnoses and potential mortality resulting from delayed treatment.